PROKRASTINASI AKADEMIK MAHASISWA DITINJAU DARI RELIGIUSITAS - A. Said Hasan Basri (UIN Sunan Kalijaga Yogyakarta, 2017)
Abstract This research aimed to examine the correlation between religiosity and the academic procastination. This study also intended to reveal the difference of college student’s religosity and the academic procastination observed from gender, etnics, and programs of study. Purposive sampling was used in this study. The subjects of this study were college students in faculty of Dakwah dan Komunikasi. They were male and female which at least 2011 to 2013 of entering years. There were 185 colleges students involved in this research, 67 males and 118 females. The results of the Pearson Correlation Analysis indicated that there were a significant and negative correlation between religiosity and the the academic procastination. With ”r” scores was 0.410, and“p”< 0.01 was 0.000. The results of independent-sample t test also indicated that there were difference between religiosity and academic procastination observed from studies program. The religiosity of PMI program was the higher than others (KPI, BKI, MD and IKS). And the higher of academic procastination was the IKS program study. Key words: Religosity, Academic Procastination.